Insights into Cystic Fibrosis Polymicrobial Consortia: The Role of Species Interactions in Biofilm Development, Phenotype, and Response to In-Use Antibiotics - Magalhães, Andreia P.; Lopes, Susana P.; Pereira, Maria O. (Frontiers in Microbiology, 2017)
Cystic Fibrosis (CF) airways disease involves complex polymicrobial infections where different bacterial species can interact and influence each other and/or even interfere with the whole community. To gain insights into the role that interactions between Pseudomonas aeruginosa in co-culture with Staphylococcus aureus, Inquilinus limosus and Stenotrophomonas maltophilia may play in infection, the reciprocal effect during biofilm formation and the response of dual biofilms towards ciprofloxacin under in vitro atmospheres with different oxygen availabilities were evaluated. Biofilm formation kinetics showed that the growth of S. aureus, I. limosus and S. maltophilia was disturbed in the presence of P. aeruginosa, under both aerobic and anaerobic environments. On the other hand, under aerobic conditions, I. limosus led to a decrease in biofilm mass production by P. aeruginosa, although biofilm-cells viability remains unaltered. The interaction between S. maltophilia and P. aeruginosa positively influenced dual biofilm development by increasing its biomass. Compared with monocultures, biomass of P. aeruginosa + S. aureus biofilms was significantly reduced by reciprocal interference. When grown in dual biofilms with P. aeruginosa, ciprofloxacin was less effective against S. aureus, I. limosus and S. maltophilia, with increasing antibiotic doses leading to drastic inhibitions of P. aeruginosa cultivability. Therefore, P. aeruginosa might be responsible for the protection of the whole dual consortia against ciprofloxacin activity. Based on the overall data, it can be speculated that reciprocal interferences occur between the different bacterial species in CF lung, regardless the level of oxygen. The findings also suggest that alterations of bacterial behaviour due to species interplay may be important for disease progression in CF infection.